Perspektivy razvitiya obshchei teorii i tekhnologii sportivnoi podgotovki i fizicheskogo vospitaniya - Balsevich, V. K. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper is to consider the reasons of the crises in the ontemporary conceptions of elite athletes sports training and in the physical education of children and teenagers at general education schools. The author offers some new ways to elaborate the general theory of a person`s motor capacities` improvement in the elite sports system as well as in physical education. He considers the possible prospects of integration for the areas of sports culture and physical education and suggests some methodological ideas to realize them.